PENGEMBANGAN MODUL PEMBELAJARAN MATEMATIKA DENGAN KERANGKA ELPSA UNTUK MENINGKATKAN EMAMPUAN BERPIKIR KRITIS SISWA PADA MATERI LOGIKA MATEMATIKA KELAS - Kartika, Yeni; Sanapiah, Sanapiah; Juliangkary, Eliska (Media Pendidikan Matematika, 2017)
The aim of this development research is producing mathematical logic module with the sketch of ELPSA to increase students’ critical thinking ability and to know quality of module according to aspects of validity, and aspects of practicality.The method that use in this research is R&D (Research and Development) by the model of ADDIE (Analysis, Design, Development, Implementation, and Evaluation).The subject of this research is developing module with the sketch of ELPSA in mathematical logic.The instrument that use to measure quality of this developing module  are questionnaire sheet for aspects of validity, teachers’ evaluation sheet for aspects of practically, students’ questionnaire responses, and achievement test to know students’ critical thinking ability.According to assessment of validator matter experts and media experts, this module is already valid which percentage scores are respectively 88.9% and 86.7% in the excellent category.The qualityof the module meets practically based teacher evaluation questionnaire with a percentage score is 78% in well category. As a result, the module is said to be practical.Students’ responses to the module are obtained by questionnaire which the average score is 44.99 in excellent category.As for knowing students’ critical thinking ability are based on the result of students’ pretest in XI grade and students’ post-test in X grade of MA NW Sepit who get average scores 54.3 and 91.2 with the percentage of completeness of 95.2% in greatly increased category.As a sequence, this research is showing the module that is developing which is able to use in learning process that use KTSP or 2013 curriculums. The quality of module reached criteria the quality of module and can improve students’ critical thinking ability in mathematical logic.